Evaluation of selected parameters of rat liver injury following repeated administration of oseltamivir for different periods - Al-Rikabi, Falah Muosa Kadhim (The Iraqi Journal of Veterinary Medicine, 2012)
The effects of oseltamivir administration, an anti influenza viruses A and B, on some functional parameters of rat liver were investigated, to evaluate the possible hepatotoxic effect. Eighteen (18) wister male albino rats with body weight ranged 150-190 gm were divided into three groups, the first group(T1) was treated orally with 1mg/kg.BW as therapeutic dose of Oseltamivir for 7consuctive days. The second group (T2) was treated with the same dose for six weeks, while the control group dosed distill water.The results revealed, there was a significant increase in the onset of barbiturate sleeping time and a significant p ≤ 0.05 decrease of the duration of barbiturate sleeping time of the T2 rats . The liver enzymes activity revealed a significant decrease in ALT in T1 rats and significant increased p<0.05 in the T2 rats, while the AST activity showed only significant increased p<0.05 in the T2 treated rats. The activity of ALP was p<0.05 significantly increased in the rats of treated groups. The blood sugar was significantly decreased p<0.05 only in the T2rats. Cholesterol level was significantly p<0.05 increased in T2 treated rats, while the serum of both treated groups showed a significantly increase p<0.05 in the triacylglycerol concentration.The HDL level was significantly decreased p<0.05 only in theT1 rats. The treated T2 rats showed a significant decrease p<0.05 in the LDL, while the VLDL level revealed a significant increase p<0.05.The total serum protein level was significantly increased p<0.05 in the rats of T2. Liver histopathological lesions of the T1rats revealed large amount of suppurative exudates, severe dilation and congestion of central veins and sinusoids with activation of kupffer cells. The liver of T2 rat showed multiple areas of focal necrosis, fibrous thickening of Glisson capsule with vacuolar degeneration of hepatic parenchyma. In:conclusion, Oseltamivir has hepatotoxic effect in rats treated with therapeutic dose 1mg/ kg.BW. orally in different periods.